A nonsense exon in the Tpm1 gene is silenced by hnRNP H and F. - Coles, J; Hallegger, M; Smith, C (2009)
As well as generating protein isoform diversity, in some cases alternative splicing generates RNAs that harbor premature termination codons and that are subject to nonsense-mediated decay (NMD). We previously identified an apparent pseudo-exon in the rat alpha-tropomyosin (Tpm1) gene as a probable genuine alternatively spliced exon that causes NMD when spliced into Tpm1 RNA. Here, we report the analysis of cis-acting splicing regulatory elements within this "nonsense exon." Guided by the data set of predicted splicing enhancer and silencer elements compiled by Zhang and Chasin, we made a series of mutations through the nonsense exon and found that like authentic exons it is densely packed with enhancer and silencer elements. Strikingly, 11 of 13 tested mutations behaved as predicted computationally. In particular, we found that a G-rich silencer at the 5' end, which is crucial for skipping of the nonsense exon, functions by binding hnRNP-H and F.